State of sediment transport and seagrass distribution under the combined action of velocity and current direction - WIDYASTUTI UMAR; HENDRA HASIM; WILMA JOANNA CAROLINA MOKA (Society for Indonesian Biodiversity, 2024)
Abstract. Umar W, Hasim H, Moka WJC. 2024. State of sediment transport and seagrass distribution under the combined action of velocity and current direction. Biodiversitas 25: 4515-4524. This research delves into the intricate dynamics of sediment transport and seagrass distribution on the West Coast of Bone Bay, Indonesia, specifically focusing on the profound influence of ocean currents. Our data, meticulously collected from Karang-Karangan, Siwa, and Sembilan Island, reveal a compelling narrative. We employed quantitative methods, including measuring ocean current speeds using Marotte current meters, which recorded velocities ranging from 0.1 to 0.5 m/s. Sediment samples were analyzed for grain size, with median sizes ranging from 233 µm (fine sand) to 626 µm (coarse sand). Sedimentation rates, a key indicator, were measured using sediment traps, recorded between 10 and 50 mg/cm²/day. Seagrass cover was assessed through line transect sampling, revealing cover percentages from 28 to 45% across the study sites. The results, a testament to the power of scientific inquiry, indicate that Sembilan Island had the highest sedimentation rates and seagrass coverage, which correlates with its unique hydrodynamic conditions, particularly the southward-directed currents. These findings underscore the critical relationship between ocean currents, sediment transport, and seagrass ecosystems, which are essential for the proposed designation of Bone Bay as a marine protected area. This research underscores the importance of combining quantitative data with a thorough understanding of environmental interactions to effectively manage and conserve coastal ecosystems. Further studies are recommended to explore the detailed mechanisms of these interactions, paving the way for a deeper understanding of our natural world.